Studying the factors affecting the karst zonation and development of Khorin Mountain using Fuzzy Logic. - Amir Saffari; Tayebeh Kiani; Sasan Zangenehtabar (تحقیقات کاربردی علوم جغرافیایی)
Karstic zones play an important role in feeding the karstic aquifers؛ therefore, recognizing the factors affecting the karst mutation and its zonation in the field of studies concerned with karst water resources is of great concern. The results of these studies can be applied to quantitative and qualitative management and protection of these resources against the pollutions coming from human activities. Karst mass of Khorin with an area of 396.5 square kilometers is located in elevated Zagros zone at the boundary of two provinces, Kurdistan and Kermanshah. Because of the outcrops of carbonate rocks and the presence of other variables, this mass in which there are many springs as karst aquifer outputs is susceptible of Karstification. Thus, identifying the karstic shapes as well as studying the geomorphology of karst and its development in the karst mass of Khorin is very significant. In this relief different forms of karst landscape including a variety of Lapies, sinkholes, caves, etc. have formed. Here, lithological layers, distance from faults, precipitation, temperature, slope, elevation, direction and plants were fuzzy considering the required function for each and then were combined using 0.9 gamma operator. At the end, the zonation map of surface karst development was prepared. This map was classified into four classes of without karst, karst with low development, karst with medium development and karst with high development through natural fractures method. Regarding the need for the layer of sinkholes, to study the accuracy of karst development zonation in the area under the survey, karst sinkholes were identified and their spatial distribution map was prepared using the Fill sink method. The results of this study indicate that about 98% of sinkholes are situated in the classes of triple karst.